2021
DOI: 10.7717/peerj.12447
|View full text |Cite
|
Sign up to set email alerts
|

Rumen bacterial community profile and fermentation in Barki sheep fed olive cake and date palm byproducts

Abstract: Rumen bacteria make the greatest contribution to rumen fermentation that enables the host animal to utilize the ingested feeds. Agro-industrial byproducts (AIP) such as olive cake (OC) and date palm byproducts (discarded dates (DD), and date palm fronds (DPF)) represent a practical solution to the deficiency in common feed resources. In this study, thirty-six growing Barki lambs were divided into three groups to evaluate the effect of untraditional diets including the AIP on the growth performance. Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 76 publications
3
13
0
Order By: Relevance
“…The findings of this study showed that the proportions of solidattached Ruminococcaceae and RC9_gut_group are higher in this study than their proportions in camel and sheep in previous studies [8,68] as well as cow [57], buffalo [69], and deer [62]. Furthermore, the relative abundance of Prevotella was lower than in other ruminant animals [8,57,62,68,69]. More details about the comparison between this study and previous studies could be found in Supplementary figure (S1 Fig).…”
Section: Analysis Of Bacterial Communitysupporting
confidence: 54%
See 1 more Smart Citation
“…The findings of this study showed that the proportions of solidattached Ruminococcaceae and RC9_gut_group are higher in this study than their proportions in camel and sheep in previous studies [8,68] as well as cow [57], buffalo [69], and deer [62]. Furthermore, the relative abundance of Prevotella was lower than in other ruminant animals [8,57,62,68,69]. More details about the comparison between this study and previous studies could be found in Supplementary figure (S1 Fig).…”
Section: Analysis Of Bacterial Communitysupporting
confidence: 54%
“…Animal species and the chemical composition of animal diet are the main determiners of the rumen microbiome [54]. The findings of this study showed that the proportions of solidattached Ruminococcaceae and RC9_gut_group are higher in this study than their proportions in camel and sheep in previous studies [8,68] as well as cow [57], buffalo [69], and deer [62]. Furthermore, the relative abundance of Prevotella was lower than in other ruminant animals [8,57,62,68,69].…”
Section: Analysis Of Bacterial Communitymentioning
confidence: 40%
“…Barki sheep breed is a crucial part of food security in arid countries due to its adaptability to desert harsh conditions; however, it lacks the appropriate feeding systems to increase its productive performance [9] . Therefore, various combinations of locally available feed resources could be used to enhance animal productivity at a low cost [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The availability of local agricultural byproducts generated the primary interest to incorporate them in animal feed to fill the gap in animal feeding and avoid the environmental consequences [7] , [9] . Large quantities of agricultural wastes such as OC, DD, and DPF are produced in arid countries; thus, these byproducts could replace the traditional feed resources [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation